Analysis of the Role of Information Technology in Driving Digital Transformation of UMKM in the Digital Economy Era in Indonesia - Sri Astuti, Dini; Asrul Hidayat; Rezky Pratama; Juniarti Iryani (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study aims to determine the effectiveness of the use of information technology in driving digital transformation in the Micro, Small, and Medium Enterprises (UMKM) sector, especially in the Bulukumba area. In the midst of the development of the digital economy, technology is a strategic factor to improve operational efficiency, expand market reach, and strengthen business competitiveness. However, the implementation of technology among UMKM is not optimal because it is still faced with various obstacles such as low digital literacy, limited devices, and lack of training. This study uses a descriptive quantitative approach with three main indicators, namely the use of information technology, digital transformation, and the performance and competitiveness of UMKM. Information technology is considered to help accelerate transactions, improve financial records, expand promotions, and encourage product innovation. Thus, the use of digital technology has proven effective in supporting the transformation of UMKM in a sustainable and competitive manner in the digital economy era.